Association of Physical Activity with Sleep and Health-related Quality of Life in Patients with Polycystic Ovarian Syndrome: A Cross-sectional Study - Jincy Samuel; GC Swastika; Ashara Maharjan; Shreya Raju Nidavani (Journal of Clinical and Diagnostic Research)
Introduction: Polycystic Ovarian Syndrome (PCOS), a condition prevalent among women in their childbearing age has been seen to impact sleep, Health-related Quality of Life (HrQoL) and Level of Physical Activity (LPA). However, not enough studies shown that how being physically active affects sleep and HrQoL in PCOS. Finding an association of physical activity with sleep and HrQoL in PCOS may be beneficial in including physical activity to improve sleep and HrQoL in PCOS. Aim: To explore an association of the LPA with sleep and to further explore an association between LPA and HrQoL in PCOS. Materials and Methods: This cross-sectional study was carried out at Department of Physiotherapy, Krupanidhi College of Physiotherapy, Bengaluru, Karnataka, India, from March 2023 to March 2024 on 270 women with PCOS in accordance to the Rotterdam criteria and aged between 18-24 years. The recruited subjects were evaluated for LPA, sleep quality and HrQoL using self-reported scales that were the International Physical Activity Questionnaire (IPAQ) scale, Pittsburg’s sleep quality scale and the Short Form Health Survey questionnaire (SF-36) scale respectively followed by statistically analysing the data using descriptive analysis, Kruskal Wallis test and Chi-square test. A p-value of less than 0.05 was considered as statistically significant. Results: The mean age of the subjects was 21.82±1.65 years. Level of being physically active was associated with all the domains of SF-36 (p<0.01) other than role limitation due to emotion (p=0.177) and domain of emotional well-being (p=0.142) where the association was non significant. Sleep quality was also associated with the LPA (p≤0.001). Conclusion: The LPA does have an association with sleep quality as well as with the physical domains of HrQoL. Thus, the level of being physically active is a determining aspect in the quality of sleep and HrQoL in PCOS. Including education and awareness on the importance of having the right LPA thereby may have an impact on sleep and HrQoL in PCOS.